Effects of Extraction Temperature on Physicochemical Properties and Antioxidant and Immunomodulatory Activities of Polysaccharides from Lycium ruthenicum Murr. - Bing LIU; Jingyu MA; Ting LI; Jun ZHU; Meipeng ZHU; Lihua WU; Xia CHEN; Xinguo ZHANG; Ping ZHAO (Shipin gongye ke-ji)
Lycium ruthenicum Murr. polysaccharides (LRPs) were obtained by the water extraction-ethanol precipitation method using extraction temperature (20, 40, 60, 80, 100 ℃) as variables. The effects of extraction temperature on the physicochemical properties of LRPs were investigated by analyzing the yield of polysaccharides, carbohydrate content, glyoxylate content, UV spectra, FT-IR spectra, relative molecular mass and monosaccharide composition. The effect of extraction temperature on the antioxidant activity of LRPs was analyzed through the detection of DPPH, ABTS+, hydroxyl radicals, superoxide anion radical scavenging activity, and the reducing ability of potassium ferricyanide. The effect of extraction temperature on the immunomodulatory activity of LRPs was investigated by analyzing the effect of LRPs on RAW264.7 cell viability and cytokine secretion. Different extraction temperatures could affect the physicochemical properties of LRPs as well as their antioxidant and immunomodulatory activities. The extraction yields of polysaccharides at 60 ℃ (LRP60, 2.38%±0.11%) and 80 ℃ (LRP80, 2.30%±0.25%) were significantly higher than those of other polysaccharides. The relative molecular masses of LRP20, LRP40, LRP60, LRP80 and LRP100 were 293.34, 227.94, 233.45, 273.53 and 233.66 kDa, respectively. LRPs were mainly composed of L-Ara, D-Gal, D-Glc, D-Man, L-Rha and D-GlcA with a small amount of D-Xyl, of which LRP80 and LRP100 contained D-GalA. The Lycium ruthenicum Murr. polysaccharides obtained by extracting at 60 ℃ and 80 ℃ temperature had good antioxidant activity and immunomodulatory activity. At an extraction temperature of 60 ℃, the proportion of D-Gal and L-Ara in the monosaccharide composition of polysaccharides increased, and the antioxidant activity was better. While the ratio of D-GlcA, D-Glc and D-GalA increased at the extraction temperature of 80 ℃, the immunomodulatory activity of Lycium ruthenicum Murr. polysaccharides was better. Therefore, LRP60 and LRP80 from Lycium ruthenicum Murr. could serve as potential natural antioxidants or immunomodulators.